Care providers, access to care, and the Long-term Care Nursing Insurance in China: An agent-based simulation. (January 2020) - Chang, Shuang; Yang, Wei; Deguchi, Hiroshi
Abstract: China piloted a publicly funded Long-term Care Nursing Insurance (LTCNI) with an aim to improve access to long-term care (LTC) for older people in China in 2012. Existing studies showed that the scheme has been successful in meeting some goals, but little is known on how the availability, price and quality of the local care providers affect access to care. Using an Agent-based Modelling approach, this paper simulates the effects of the LTCNI on access to care by considering quality, costs and availability of the local care providers. Our simulation is based on Qingdao city—the first city in China that piloted the LTCNI. We found considerable discrepancies in terms of access to services among the LTCNI beneficiaries. The poor are more likely to choose nursing home care with low costs albeit these services may be of poor quality. The demand for home-based services is high, but these services are not distributed according to population needs and are not available in some districts with high concentration of older people. Consequently, a large proportion of disabled older people have no access to home-based services. We urge policy makers to improve the benefit package of the LTCNI, especially for the poor. We also suggest that more resources should be directed to promote and improve the availability of home-based services in areas with a large number of older people. Highlights: Evaluate the effects of Long-term Care Nursing Insurance (LTCNI) on access. Use an innovative Agent-based Modelling approach. Considerable discrepancies are observed for access to care among the beneficiaries. The poor are more likely to choose nursing home with low costs and poor quality. Important to promote home-based care in areas with high LTC demand.